2009
DOI: 10.1590/s0101-20612009000300029
|View full text |Cite
|
Sign up to set email alerts
|

Minerals and essential fatty acids of the exotic fruit Physalis peruviana L.

Abstract: *A quem a correspondência deve ser enviada Minerals and essential fatty acids of the exotic fruit Physalis peruviana L. Minerais e ácidos graxos essenciais da fruta exótica Physalis peruviana L.Eliseu RodRIguES 1 , Ismael Ivan RoCkENbACh 1 *, Ciriele CATANEo 1 , Luciano Valdemiro goNzAgA 1 , Eduardo Sidinei ChAVES 2 , Roseane FETT 1 1 Introduction high production of several native and exotic fruits in brazil is due to its large territory and its presence in areas of tropical and temperate climates (gRANAdA;zAm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
7
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 2 publications
6
35
7
12
Order By: Relevance
“…Leterme et al [20] determined that the mineral composition of P. peruviana was Ca (23 mg/100g), Mg (19 mg/100g), Fe (0.09 mg/100g), and Zn (0.28 mg/100g). In addition, Rodrigues et al [21] reported that the mineral content in P. peruviana fruit consumed from Brazil was Ca (9.00 mg/100g), Fe (1.47 mg/100g), Mg (34.70 mg/100g), Cu (0.28 mg/100g). and Zn (0.49 mg/100g).…”
Section: Discussionmentioning
confidence: 99%
“…Leterme et al [20] determined that the mineral composition of P. peruviana was Ca (23 mg/100g), Mg (19 mg/100g), Fe (0.09 mg/100g), and Zn (0.28 mg/100g). In addition, Rodrigues et al [21] reported that the mineral content in P. peruviana fruit consumed from Brazil was Ca (9.00 mg/100g), Fe (1.47 mg/100g), Mg (34.70 mg/100g), Cu (0.28 mg/100g). and Zn (0.49 mg/100g).…”
Section: Discussionmentioning
confidence: 99%
“…In Ecuador, P. peruviana is produced in the provinces of Azuay, Carchi, Cotopaxi, Imbabura and Pichincha, counting over 200 hectares in 2011 [89]. Despite its potential, in most countries P. peruviana is a backyard plant, nevertheless in some international markets such as Europe, the fruits have recently reached very high prices [90]. They are usually consumed as fresh fruit, however, they can also be served in salads, cooked dishes, desserts, jams, natural snacks, and canned fruit [75,81].…”
Section: Agronomic Aspectsmentioning
confidence: 99%
“…In Brazil, is popular in the Northern and Northeastern regions while in Southern and Southeastern it has a still recent cultivation (RODRIGUES et al 2009), which is expanding, particularly in the Rio Grande do Sul State where the plant can be exploited by small-scale producers (MUNIZ et al, 2014). The world's largest production of cape gooseberry occurs in Colombia, a country that suffers with salinity problems in about 600,000ha of its agricultural area (MIRANDA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%